Diário de bordo: uma construção colaborativa rumo à Pedagogia Cultural - Alcântara, Cristiano Rogério (2015)
This study, carried out in two municipal public schools in a city of São Paulo s Grand Metropolitan Area, makes use of collaborative research, trying to present the pedagogical coordination s possibility of introducing the mediation of cultural objects and device toward the development of Cultural Pedagogy based on Jerome Bruner s theories. The research s evolution is told on a Benjaminian perspective, where experience is maximally contextualized, in an attempt to embrace varied points of view about all involved actors and questioning the consequences of the mediation presented preferably in groups. The Collective Pedagogical Working Hours (CPWH), thought as the only possible suitable moment for a mediation site between coordinator and group, will be contextualized starting from the reading of the logbooks written by the professionals and will be the framing axis of the pedagogical coordination s mediation, as well as a privileged tool to follow up and assess the propositions put forward to the group. From the dialogues that emerged among texts written by the professionals and the coordinator s feedbacks an interlocution gets started, where the other is seen as responsible and collaborator in aesthetic experience and pleasure choices, beyond the awareness of popularized Culture, searching for an Aesthetics of fracture recommended by Algirdas Julien Greimas. The presentation of cultural objects and device, always based on Ethic conjunctures and the Theory of Communicative Actions by Jurgen Habermas, together with Van Dijk s Mental Models, provide the elements for a careful analysis of a teacher s written topics. This thesis is presented in five chapters that look for reconstructing the pedagogical coordinator s path to mediate and valorize cultural objetcs and device to professionals under his responsibility, making use of a narrative of his initial procedures and ending up in a description of what he understands as Cultural Pedagogy